The infralimbic cortex regulates the consolidation of extinction after cocaine self-administration - LaLumiere, Ryan T. (Cold Spring Harbor Laboratory Press, 2010)
The infralimbic cortex (IL) regulates the consolidation of extinction learning for fear conditioning. Whether the IL influences the consolidation of extinction learning for cocaine self-administration is unknown. To address this issue, male Sprague–Dawley rats underwent 2 wk of cocaine self-administration followed by extinction training. On the first 5 d of extinction, rats underwent brief (15- or 30-min) extinction sessions and received intra-IL microinjections immediately after each extinction session. On days 6–12 of extinction, rats underwent full-length (2-h) extinction sessions that were used to assess the retention of the extinction learning from the short sessions. IL inactivation via microinjections of the GABA agonists baclofen and muscimol (BM) immediately after the extinction sessions (days 1–5) impaired the retention of extinction learning. Control experiments demonstrated that this effect was not due to inactivation of the prelimbic cortex or due to effects of the drugs on the subsequent day's behavior. In contrast, post-training intra-IL microinjections of the allosteric AMPA receptor potentiator 4-[2-(phenylsulfonylamino)ethylthio]-2,6-difluorophenoxyacetamide (PEPA) enhanced retention of the extinction learning. As evidence suggests a role for the β-adrenergic receptors in memory consolidation, other rats received microinjections of the β(2)-adrenergic receptor agonist clenbuterol or antagonist ICI-118,551 (ICI). Post-training intra-IL administration of clenbuterol or pre-training administration of ICI enhanced or impaired, respectively, the retention of extinction learning. These data indicate that the IL, and specifically the glutamatergic and β-adrenergic systems in the IL, regulates the consolidation of extinction of cocaine self-administration and that the IL can be manipulated to influence the retention of extinction.